Inflammatory Myofibroblastic Tumor of the Hilar Bile Duct: A Case Report and Literature Review - Gao, Sheng-qiang; Bao, Yong-jin; Luo, Jian-sheng (Frontiers in Surgery, 2022)
Background: Inflammatory myofibroblastic tumor (IMT) is a very rare tumor and occurs seldom in the biliary tract. IMT can occur in any part of the body and in people of any age; however, it most commonly occurs in children or adolescents. Its etiology and pathogenesis are currently unknown. The clinical manifestations of a hilar inflammatory myofibroblastic tumor are atypical, and the imaging examination is nonspecific. The diagnosis is mainly based on histopathology and immunohistochemistry findings, and surgical resection is the preferred treatment method. Case Description: Herein, we report a rare case of hilar bile duct IMT and review the related literature. Our patient was a 54-year-old woman presenting with a 1-day history of upper abdominal pain as the main clinical symptom. She was misdiagnosed as having cholangiocarcinoma before the surgery. She underwent surgery and was ultimately diagnosed with IMT based on histopathology and immunohistochemistry findings. On 1-year follow-up, no tumor recurrence or related complications were noted. Conclusions: We hope this case report helps clinicians gain a deeper understanding of biliary IMT of the hilum.